Case study of a patient with chronic urticaria and its differential diagnoses (International Seven Journal of Health Research, 2023)
Urticaria is a chronic or acute condition that presents with angioedema and/or hives. It is a common health problem with various possibilities in terms of triggering factors. Among these factors, for this research, autoimmune diseases stand out. In the case of the patient in this case report, Hashimoto's thyroiditis and systemic lupus erythematosus were considered as points of analysis, given the clinical and exam findings. The former is an autoimmune disease that affects the thyroid, with IgE as a common point with urticaria. As for lupus, the lesions in extreme cases of the disease have many similarities to the lesions of urticaria. For the diagnosis and treatment of urticaria, knowledge of associated diseases is of great importance, seeking greater diagnostic accuracy and specific knowledge of each pathology, so it is essential to disseminate characteristic findings in specific cases.